KEMAMPUAN LITERASI PESERTA DIDIK PENDIDIKAN JASMANI DI SMK - Nurhadiansyah, Reza; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIn this study researchers want to do understanding and level of student literacy in learning 13 with indicators of listening, writing, reading so that students understand more about what they will get during learning.The method used in the research is dikriftif namely by describing a percentage of the level of literacy in students at the time of study with the subject of research students and female students of class X felt a sense of success.The results showed that students' understanding of physical education literacy was very good 142-163 with a frequency of 20 percent 20,%, both 120-141 with a frequency of 70 and a percentage of 70,% 98-119 frequency 10 with a percentage of 10,% and very less 76- 97 fringe 0 with a percentage of 00,% means the category is lacking.Keywords: Literacy, Phycical Education